Paper electronic literature : an archaeology of born-digital materials - Gibson, Richard Hughes (Page and screen., 2021)
"The field of electronic literature has a familiar catchphrase, "You can't do it on paper." But the field has in fact never gone paperless. Reaching back to early experiments with digital writing in the mainframe era and then moving through the personal computer and Internet revolutions, this book traces the changing forms of paper on which e-lit artists have drawn, including continuous paper, documentation, disk sleeves, packaging, and even artists' books. Paper Electronic Literature attests that digital literature's old media elements have much to teach us about the cultural and physical conditions in which we compute; the creativity that new media artists have shown in their dealings with old media; and the distinctively electronic issues that confront digital artists. Moving between avant-garde works and popular ones, fiction writing and poetry generation, Richard Hughes Gibson reveals the diverse ways in which paper has served as a component within electronic literature, particularly in facilitating interactive experiences for users. This important study develops a new critical paradigm for appreciating the multifaceted material innovation that has long marked digital literature"--